First Incidence of Peste des Petits Ruminants Virus in Cervidae Family from State Zoo of Assam, India - Nagendra Nath Barman; Arpita Bharali; Durlav Prasad Bora; Biswajit Dutta; Mousumi Bora; Sophia M. Gogoi; Panchami Sharma; Sankar Sarma; Parikshit Kakati; Tejas Mariswamy; Ankita Choudhury; Lukumoni Buragohain (Viruses)
The present study aimed to investigate the episodes of per-acute mortality due to peste des petits ruminants (PPR) that resulted in the death of 30 animals of different species of cervids, namely, barking deer, four-horned antelope, hog deer, thamin, and mouse deer in the State Zoo of Assam, a northeastern state of India. The affected animals showed no to limited clinical signs. However, the necropsy and histopathological findings were highly suggestive of PPR virus (PPRV) infection observed in domestic small ruminants. Representative tissue samples were screened for the presence of PPRV along with blue tongue virus (BTV) and epizootic hemorrhagic disease virus (EHDV) using RT-PCR or RT-qPCR and were found to be positive for PPRV. Considering the sudden outbreak of PPR in captive cervids, we sought to determine the role of domestic goats as the potential spillover host. To verify that, archived tissue samples of domestic goats collected during PPRV outbreaks in nearby localities and slaughtered goats used as meat for Carnivorous animals in the State Zoo were also screened and found to be positive for PPRV in RT-PCR. Phylogenetic analysis based on the Nucleocapsid (N) protein gene of PPRV from infected cervids, domestic goats, and goat meat revealed the virus to be of Lineage IV origin. Our findings provide evidence of probable spillover of PPRV from domestic goats to captive endangered cervids and circulation of Lineage IV PPRV strains among the small-ruminant population of this region.